2013
DOI: 10.1016/j.mrgentox.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and cytotoxicity in adult subjects with prediabetes

Abstract: Prediabetes (intermediate hyperglycemia) is a high-risk state for diabetes that is defined by higher than normal glycemic levels that are below the level required for a diagnosis of diabetes. Prediabetes is characterized by oxidative stress, yet the associated DNA damage and cytotoxicity remain unknown to date. Therefore, we evaluated the relationship between glycemic alterations, DNA damage and cytotoxicity in the lymphocytes of individuals with pre-diabetes. Fasting plasma glucose (FPG) and glycated hemoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 50 publications
0
18
0
5
Order By: Relevance
“…It has been reported that diabetes is associated with an increased production of reactive oxygen species and greater oxidative damage to DNA [32,33]. Recently, it has also been reported that the overall frequency of DNA damage and cytotoxicity correlates with the level of HbA 1c in people with prediabetes [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that diabetes is associated with an increased production of reactive oxygen species and greater oxidative damage to DNA [32,33]. Recently, it has also been reported that the overall frequency of DNA damage and cytotoxicity correlates with the level of HbA 1c in people with prediabetes [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that there is no increase in DNA damage in DM2 [21, 22]. Other studies have indicated that an increase in micronuclei will not likely occur in early DM2 [23], but only in uncompensated DM2 (i.e., A1C > 8%) [24]. In our study, only 4 (approximately 6%) out of the 70 subjects had uncompensated DM2 (A1C > 8.0%); therefore, it was not likely that the sample would present an increase in chromosomal DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, other parameters that could affect the frequency of MN and NAs, such as prediabetes, metabolic syndrome, or obesity, which are also related to inflammatory processes and DNA damage, were not considered [4,15,37,[45][46][47][48][49][50][51].…”
Section: Effects Of Dmmentioning
confidence: 99%